2014
DOI: 10.1108/jea-10-2012-0110
|View full text |Cite
|
Sign up to set email alerts
|

Development and validity of the Ethical Leadership Questionnaire

Abstract: Purpose – This study had five objectives: explain the initial steps that led to the construction of the Ethical Leadership Questionnaire (ELQ); analyze the items and verify the ELQ reliability using item response theory (IRT); examine its factorial structure with a confirmatory factor analysis (CFA) and an exploratory structural equation modeling (ESEM) approach; test the item bias of the ELQ; assess the relation between the ELQ dimensions and ethical sensitivity. The paper aims to discuss thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 38 publications
2
63
0
1
Order By: Relevance
“…Another secondary outcome was Ethical Leadership, assessed used the Ethical Leadership Questionnaire (ELQ; Langlois et al., 2014). The ELQ was developed for leadership research in education, business and public administration settings.…”
Section: Methodsmentioning
confidence: 99%
“…Another secondary outcome was Ethical Leadership, assessed used the Ethical Leadership Questionnaire (ELQ; Langlois et al., 2014). The ELQ was developed for leadership research in education, business and public administration settings.…”
Section: Methodsmentioning
confidence: 99%
“…Presently, an increasing number of researchers are trying to research the ethical dimensions of leadership, including education (Langlois et al, 2014). Furthermore, in recent years, the ethics of practice has been a popular topic of discussion in many professional fields, including education (Kocabas & Karakouml, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the aforementioned issues, a substantial and growing body of research is found in the recent literature that is aimed at developing an understanding regarding the ethical dimensions of leadership in schools (Arar et al, 2016;Langlois et al, 2014) and of the role of leadership in school change (Fullan, 2011;Hallinger, 2003;Leithwood et al, 2008). However, only a small number of these studies focussed on leaders' ethical practices in times of change (Burnes and By, 2012).…”
Section: Introductionmentioning
confidence: 99%